EVALUATING THE EFFECTIVENESS OF THE TREE OF LIFE INTERVENTION ON AGGRESSION MANAGEMENT AND ACADEMIC PERFORMANCE ENHANCEMENT AMONG ADOLESCENTS IN SELECTED SCHOOLS, CHENNAI - Mrs. Rejili Grace Joy. M; Dr. Kayalvizhi. E; Dr. Hemavathy. J; Mrs. Vahitha Mala K (The Bioscan, 2024)
Background: This study investigates the Tree of Life intervention’s effectiveness in managing aggression and enhancing academic performance among adolescents. By fostering resilience and self-esteem through narrative therapy, the intervention aims to empower students to reduce aggression, ultimately improving their educational outcomes and creating a more supportive learning environment. Aim: The study evaluates the Tree of Life intervention’s effectiveness in managing aggression and enhancing academic performance among adolescents, supporting better behavioral and educational outcomes. Methods: Utilizing a true experimental pretest-posttest control group design, the study was conducted in selected schools in Chennai, Tamil Nadu, targeting adolescents aged 13-16 years. Sixty participants, evenly divided by gender and grade (8-10), were randomly assigned to an experimental group (Tree of Life intervention) or a control group. Data collection included demographic questionnaires, the Modified Buss-Perry Aggression Questionnaire, and academic performance assessments. The intervention lasted four weeks, featuring weekly 60-minute sessions encouraging personal reflection through creative activities, while the control group maintained regular routines. Findings: The demographic analysis revealed comparable distributions across both groups, with the experimental group exhibiting a higher prevalence of mild aggression. Posttest scores indicated substantial improvements in the experimental group, supported by a significant p-value of 0.001, demonstrating the intervention’s effectiveness. A negative correlation between aggression and academic performance was observed, indicating that as aggression levels decrease, academic performance improves. Conclusion: The Tree of Life intervention significantly reduced aggression and enhanced academic performance among adolescents. The control group’s lack of change underscores the intervention’s effectiveness, suggesting its potential benefits for student well-being and academic success in schools. Further research should explore long-term effects and additional influencing factors.